Ultrasound Enhances the Expression of Brain-Derived Neurotrophic Factor in Astrocyte Through Activation of TrkB-Akt and Calcium-CaMK Signaling Pathways. (1st June 2016) - Liu, Shing-Hwa; Lai, Yi-Long; Chen, Bo-Lin; Yang, Feng-Yi
Abstract: Low-intensity pulsed ultrasound (LIPUS) stimulation has been shown to increase the expression of brain-derived neurotrophic factor (BDNF) in astrocytes of an in vitro model and rat brains of an in vivo model; however, their molecular mechanisms are still not well clarified. Here, we investigated the underlying mechanisms of BDNF enhancement by LIPUS in rat cerebral cortex astrocytes. After LIPUS stimulation in astrocytes, the protein and mRNA expressions were measured by western blot and RT–PCR, respectively. The concentration of intracellular calcium was determined spectrophotometrically. The results showed that LIPUS enhanced the phosphorylation of tropomyosin-related kinase B (TrkB) and Akt but had no effect on Erk1/2 phosphorylation. Additionally, LIPUS increased the intracellular concentration of calcium and enhanced the protein levels of calmodulin-dependent kinase (CaMK) II and CaMKIV. LIPUS also activated the phosphorylation of NF-κB-p65 but did not promote the activation of cAMP response element-binding protein (CREB). Taken together, our results suggest that LIPUS stimulation upregulates BDNF production in astrocytes through the activation of NF-κB via the TrkB/PI3K/Akt and calcium/CaMK signaling pathways. BDNF has emerged as a major molecular player in the regulation of neural circuit development and function. Therefore, LIPUS stimulation may play a crucial and beneficial role in neurodegenerative diseases.